Efeito da água tratada magneticamente na mistura de concreto utilizando cimento portland cp II-Z-32-RS - Teixeira, Miqueias Alves (Universidade Federal Rural do Semi-Árido, 2018)
The development of special concretes has been the focus of many researchers and, in the last decade, there has been a growing number of studies about the use of magnetic treatment in water for concrete mixing, increasing its workability and resistance to compression. The development of special concretes has been the focus of many researchers and, in the last decade, there has been a growing number of studies about the use of magnetic treatment in water for concrete mixing, increasing its workability and resistance to compression. Therefore, the focus of this work is to analyze the effect that the magnetically treated water (MTA) has on the concrete, considering the geometry of the magnets used to generate the field. For this purpose, a total of 18 specimens of concrete with the same proportion of the constituent elements of the mixture were produced, being divided into three groups: the control group (CPcont.), Whose water of the mixture was not subjected to magnetic treatment; the test group with magnets of geometry L (CPL), whose water has undergone magnetic field action from magnets with geometry in the form of letter L (HD magnets); and the test group with ring geometry magnets (CPanel), whose water was submitted to the field from magnets with ring- shaped geometry (conventional sound magnets). The development of special concretes has been the focus of many researchers and, in the last decade, there has been a growing number of studies about the use of magnetic treatment in water for concrete mixing, increasing its workability and resistance to compression. Therefore, the focus of this work is to analyze the effect that the magnetically treated water (TM) has on the concrete, considering the geometry of the magnets used to generate the field. For this purpose, a total of 18 specimens of concrete with the same proportion of the constituent elements of the mixture were produced, being divided into three groups: the control group (CPcont.), Whose water of the mixture was not subjected to magnetic treatment; the test group with magnets of geometry L (CPL), whose water has undergone magnetic field action from magnets with geometry in the form of letter L (HD magnets); and the test group with ring geometry magnets (CPanel), whose water was submitted to the field from magnets with ring-shaped geometry (conventional sound magnets). The magnetic field performance in the last two groups was 24 hours, before the concrete production. The workability was evaluated through the slump test, for later comparison between the groups. Mechanical compression strength tests were performed at 7 days and at 28 days of age. The results obtained so far demonstrate that the concretes produced with magnetically treated water show increased workability, as verified in the literature. In relation to the compressive strength, the increase in CPL and CPanel, when compared to CPcont., Was obtained in the CPanel group, increasing by almost 15%. relation to those made with ordinary water. In view of these results, this increase proves viable for the future development of a new technique.
Monografia
Keywords: Água tratada magneticamente; Concreto especial; Resistência à compressão; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA